University students’ cognitive flexibility and critical thinking dispositions - Karakuş, İsmail (Frontiers in Psychology, 2024)
The purpose of this study is to examine whether there are differences in critical thinking dispositions and cognitive flexibility among university students based on gender, grade level, and faculty. Additionally, the study will investigate the relationship between these two concepts and their predictive power. The study was conducted using a relational survey model and included 366 university students selected through maximum diversity sampling. The study involved university students from various faculties and grade levels. Data was collected through a personal information form, cognitive flexibility inventory, and critical thinking disposition scale. The data was analyzed using the SPSS 25 program. The results indicate that university students exhibit relatively high levels of cognitive flexibility and critical thinking tendencies. Above the medium level, there was a significant positive relationship between cognitive flexibility and critical thinking tendency. Cognitive flexibility was found to be a significant predictor of critical thinking dispositions, positively and significantly predicting critical thinking disposition and explaining 40% of it. Individuals with critical thinking tendencies exhibit cognitive flexibility, which is also associated with thinking critically. Therefore, cognitive flexibility and critical thinking are interrelated characteristics.